Commentary: from the state law monopoly to the social theory of collectivities. Issue 3 (2nd September 2018) - Marschelke, Jan-Christoph
Abstract: This commentary argues that legal pluralism research should be in thorough conversation with social theory. Practice theory and theories of network and community seem to be the most interesting candidates for this exchange. In this conversation, however, ethnographic legal studies should be careful not to lose track of the law and of normativity.